Pengembangan KIT Matching Card Sebagai Asesmen Formatif Dalam Materi Bangun Datar Pada Peserta Didik Kelas V SD Negeri 03 Pontianak Kota - Ambarwati, Tria; Hairida, Hairida; Bistari, Bistari; Muskania, Ricka Tesi; Prasodjo, Bayu (UNIB Press, 2025)
Assessment in mathematics learning is often limited to worksheets completed individually by students under the supervision of the teacher. The use of less varied assessment methods results in low student engagement, interest, and motivation in learning. Providing engaging assessment tools is one effort to create an enjoyable learning atmosphere. The KIT Matching Card is a medium that can be used as an assessment tool in learning. The KIT Matching Card is a learning medium in which students match cards consisting of two parts: question cards and answer cards, which are paired by the students to match the question with the correct answer. This study uses the Research and Development (R&D) method by applying the 4D development model. The validity results of the developed media meet the criteria for being highly valid, with an average percentage of 96.82% for the material aspect and 98.99% for the media aspect. The limited trial development using the KIT Matching Card meets the criteria for being highly effective as a learning medium, with an average percentage of 94.44% in teacher responses and 86.45% in student responses. Therefore, the KIT Matching Card is not only considered theoretically and technically valid but is also deemed practically beneficial by users in the classroom.